Pengaruh Spiritualitas Islam dan Etika Kerja Terhadap Komitmen Organisasional Dengan Kepuasan Kerja Sebagai Variabel Mediasi (Studi Karyawan Sektor Jasa Keuangan dan Asuransi di Jawa Barat) - Syifa, Noor (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
The purpose of this research is to determine the influence of Islamic Spirituality and Work Ethics on Organizational Commitment by examining Job Satisfaction as a mediating variabel on Employees of the Financial Services and Insurance City in West Java. This research is quantitative using primary data. Data analysis was carried out using 100 questionnaires processed with SPSS 27 which showed that Job Satisfaction (Z) was able to mediate the influence of Islamic Spirituality (X1) and Work Ethics (X2) on Organizational Commitment (Y). There is a limitation in this research which is the proportion of the number of research samples. which is less evenly distributed in workplace locations which are still centered in Greater Bandung and employment sectors which are still centered in Conventional Commercial Banks, Rural Banks and Other Financing Institutions. The nature of employees in the Financial Services and Insurance Sector required them to comply with lots of ethical standards. Therefore, Islamic Spirituality and Work Ethics need to be facilitated and encouraged to increase Job Satisfaction which has an impact on Organizational Commitment in a way to achieve organizational purposes.